Three-year follow-up study of respiratory and systemic manifestations of chronic obstructive pulmonary disease - Ferrari, R. [UNESP]; Tanni, S. E. [UNESP]; Faganello, M. M.; Caram, L. M. O. [UNESP]; Lucheta, P. A. [UNESP]; Godoy, I. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
Few studies show patient outcomes over time in chronic obstructive pulmonary disease (COPD). In the present study, we monitored forced expiratory volume in the first second (FEV1) and other manifestations of the disease over 3 years in 133 COPD patients (69% males, age = 65 ± 9 years, FEV1 = 59 ± 25%) evaluated at baseline. During follow-up, 15 patients (11%) died and 23 (17%) dropped out. Measurements for 95 (72%) COPD patients alive after 3 years were analyzed. FEV1, body mass index (BMI), 6-min walking distance (6MWD), Medical Research Council scale (MRC), Saint George s Respiratory Questionnaire (SGRQ), Charlson Comorbidity index, and BODE index were obtained at baseline and after 3 years. At baseline, 17 patients (18%) presented mild, 39% moderate, 19% severe, and 24% very severe COPD. Predicted FEV1 % and BMI did not change over the period (P > 0.05). FEV1 in liters [1.25 (0.96-1.72) vs 1.26 (0.88-1.60) L; P < 0.001], 6MWD (438 ± 86 vs 412 ± 100 m; P < 0.001), MRC [1 (1-2) vs 2 (1-3); P = 0.002], Charlson index [3 (3-4) vs4 (3-5); P = 0.009], BODE index (2.2 ± 1.8 vs 2.6 ± 2.3; P = 0.008), and total SGRQ (42 ± 19 vs 44 ± 19%; P = 0.041) worsened after 3 years compared to baseline measurements. These data show that COPD patients deteriorated during the 3-year follow-up despite the fact that they had only minor modifications in airway obstruction and body composition. They support the need for comprehensive patient assessment to better identify disease progression.
Keywords: Chronic obstructive pulmonary disease; Markers of disease severity; Quality of life; Exercise capacity; BODE Index